2011
DOI: 10.12659/msm.881795
|View full text |Cite
|
Sign up to set email alerts
|

Underlying diseases in syncope of children in China

Abstract: SummaryBackgroundSyncope accounts for about 1–2% of emergency department visits, but the etiology in many patients with syncope is unclear. Recently, with the use of the head-up tilt test (HUT), the number of patients with unexplained syncope (UPS) has been decreasing; however, the spectrum of underlying diseases of syncope in children is unclear. This retrospective study aimed to analyze the spectrum of underlying diseases in children with syncope.Material/MethodsThis multi-center clinical study consisted of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
24
0
6

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 18 publications
3
24
0
6
Order By: Relevance
“…However, in future studies, we need to investigate the diagnostic value in children of different ages and sex. In the present study, we reported on a relatively young group of children having POTS, which was in accordance with the published information in some references, 15,[29][30][31][32][33] although POTS often occurs in adolescents and adults. There are few studies indicating the standard dose of midodrine in pediatric medicine.…”
Section: Discussionsupporting
confidence: 92%
“…However, in future studies, we need to investigate the diagnostic value in children of different ages and sex. In the present study, we reported on a relatively young group of children having POTS, which was in accordance with the published information in some references, 15,[29][30][31][32][33] although POTS often occurs in adolescents and adults. There are few studies indicating the standard dose of midodrine in pediatric medicine.…”
Section: Discussionsupporting
confidence: 92%
“…The results of the present study showed that syncope was (15,(20)(21)(22). All the above-mentioned studies revealed the increased female prevalence of syncope in adolescents.…”
Section: Discussionsupporting
confidence: 62%
“…Although V VS is the most common cause of pediatric syncope, cardiac syncope does represent 1.5% to 6% of pediatric cases (usually defined as up to 18 years of age). 617,619,620,629,631,632 Characteristics of presenting signs and symptoms differentiating V VS from cardiac causes of syncope are generally similar to those in adults. A family history of V VS and early SCD should be sought.…”
Section: Pediatric Syncope: Recommendationsmentioning
confidence: 83%